1986
DOI: 10.1007/bf00292926
|View full text |Cite
|
Sign up to set email alerts
|

Sedation in intensive care: morphine and renal function

Abstract: Intravenous morphine infusions have been administered to 12 critically-ill patients during controlled ventilation. Acute oliguric renal failure was present in 4 patients, who were treated with a combination of haemofiltration and haemodialysis. Severity of physiological disturbance was assessed using a modified APACHE Score, level of sedation by a linear-analogue scale, and blood morphine levels by high-pressure liquid chromatography. Morphine clearance was impaired in renal failure, and was dependent on haemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…1,16,17 Most of the patients in intensive therapy need analgesia, sedation or both, and these are administered in 30 to 50% of seriously ill patients. 1 In recent national survey carried out by the Brazilian Intensive Care Association, 18 fentanyl was the analgesic agent most often used by Brazilian specialists.…”
Section: Discussionmentioning
confidence: 99%
“…1,16,17 Most of the patients in intensive therapy need analgesia, sedation or both, and these are administered in 30 to 50% of seriously ill patients. 1 In recent national survey carried out by the Brazilian Intensive Care Association, 18 fentanyl was the analgesic agent most often used by Brazilian specialists.…”
Section: Discussionmentioning
confidence: 99%
“…13 Renal replacement therapies might influence morphine clearance, producing a decrease in morphine plasma concentration of 75% with hemofiltration and 45% with dialysis. 15 These techniques appear to extract both morphine and M6G efficiently; M6G is able to pass easier through artificial kidney membrane. 31 Critically ill patients with severe renal failure who required hemofiltration or hemodiafiltration with high-efficiency or highflux membranes while receiving an intravenous infusion of morphine were studied.…”
Section: Morphinementioning
confidence: 98%
“…The infusion protocol was based on pharmacokinetic data from critically ill patients, and was geared to achieve and maintain a blood concentration of around 1 pg.ml-' [q. In fact all patients were excessively sedated at this concentration, probably reflecting their severity of illness (APACHE I1 mean 23; range 15-3 1) since it has been shown that the higher a patient's APACHE I1 score the less will be the sedation requirement [14]. At the end of the study period, propofol infusion rates were reduced to clinically appropriate rates.…”
Section: Time (H)mentioning
confidence: 99%